Study of Clinical Characteristics and Cytokine Profiles of Asthmatic Children with Rhinovirus Infection during Acute Asthma Exacerbation at National Hospital of Pediatrics. (23rd August 2018) - Nguyen-Thi-Dieu, Thuy; Le-Thi-Thu, Huong; Le-Thi-Minh, Huong; Pham-Nhat, An; Duong-Quy, Sy
Abstract : Background . In children with asthma, the viral infection of airways is usually a main cause of acute asthma exacerbation and hospitalization. However, few studies on clinical and biomolecular characteristics of asthmatic children in this field have been done, especially in emergent countries. Objective . This study described the clinical and biological characteristics of asthmatic children who had acute asthma exacerbation and rhinovirus (RV) infection. Methods . Children under 15 years of age hospitalized for acute asthma exacerbation were included. They underwent clinical examination and peripheral blood analyses for the cytokine profile. The severity of acute asthma exacerbation was evaluated by Pediatric Asthma Score (PAS). Healthy children under 15 years of age were also invited in this study. Results . One hundred fifteen asthmatic children were included in this study. There were 18.2% of mild PAS, 37.4% of moderate PAS, and 44.4% of severe PSA. Among them, 63/115 (54.8%) asthmatic children had positive RV infection (RV + ). The percentages of asthmatic children with RV + had increased polymorphonuclear leucocytes were significantly higher than asthmatic children with RV − . There were no significant differences of the concentrations of non-Th2-related cytokines in asthmatic children with RV − and RV + . The concentration of Th2-related cytokines (IL-5 and IL-13) in asthmatic children with RV + was significantly higher than those with RV − . However, there was no significant difference for the cytokine profile between mild, moderate, and severe asthma. Conclusion . RV infection is a main cause of acute asthma exacerbation in children with asthma. The increase of Th2-related cytokines, especially IL-5 and IL-13, is a relevant biomarker for RV infection in asthmatic children with severe exacerbation.